Persepsi Pedagang Terhadap Produk Pembiayaan Usaha Bank Syariah di Pasar Bulak Banteng Surabaya - Abdurrohim, Faruk; Robi'in, M (Dalwa Islamic Economic Studies: Jurnal Ekonomi Syariah, 2022)
Working capital financing or syariah financing is a financing facility provided to individuals, business entities or legal entities for working capital needs. The purpose of this study is to analyze the knowledge and profession togethet to influence traders’ perceptions of Islamic business financing products. The research method used ia a quantitative method. The test results prove there is a dominant influence between knowledge of business financing products. Through the calculation results that have been carried out obtained a significant level of 0.001 results is smallet than 0.005 meaning that there is a significant influence between knowledge of business financing products on traders in the bull bull market. Furthermore, the test results prove there is a dominant influence between professions on business financing products. Through the results of calculations that have been carried out, the significance level of the results of 0.003 is less than 0.05. which means that there is a significant influence between the profession on business financing products for trafers on the bull market.